1983
DOI: 10.1203/00006450-198305000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Neuropathologic Effects of E. coli Endotoxin in Neonatal Dogs

Abstract: Summarytional 2 0 4 samples of arterial blood were obtained hourly forThe acute systemic and neuropathologic effects of E. coli endotoxin were determined in neonatal dogs. Administration of sublethal (LDo), moderate (LD50), or lethal (LDlo0) doses of endotoxin produced significant arterial hypotension, metabolic (lactic) acidosis, and hypoglycemia. Neuropathologic changes consisted of widespread inflammation in both grey and white matter; however, necrotic lesions were found only in forebrain white matter.dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Thus, a distinct disturbance of vascular endothelium can be produced by endotoxin, as observed in brains of newborn kittens that developed PVL after endotoxin injection (122,164,165). Additionally, endotoxin has been shown to cause arterial hypotension in newborn dogs, in sublethal doses, and to produce in the same animals periventricular WM injury (166). Moreover, in the model the deficits in blood flow and metabolism produced in cerebral WM by hemorrhage-induced hypotension were similar to those produced by endotoxin-induced hypotension.…”
Section: Maternal/fetal Infection or Inflammation And Cytokine Releasmentioning
confidence: 97%
“…Thus, a distinct disturbance of vascular endothelium can be produced by endotoxin, as observed in brains of newborn kittens that developed PVL after endotoxin injection (122,164,165). Additionally, endotoxin has been shown to cause arterial hypotension in newborn dogs, in sublethal doses, and to produce in the same animals periventricular WM injury (166). Moreover, in the model the deficits in blood flow and metabolism produced in cerebral WM by hemorrhage-induced hypotension were similar to those produced by endotoxin-induced hypotension.…”
Section: Maternal/fetal Infection or Inflammation And Cytokine Releasmentioning
confidence: 97%
“…However, these neonatal dogs had necrotic lesions only in the forebrain white matter. 40 Recently developed models aim to connect the impact of maternal inflammation and fetal exposure to the inflammatory milieu (animal models of maternal inflammation-induced fetal injury are depicted in Table I). Yoon et al 41 introduced E. coli into the cervix of pregnant rabbits on gestational day 21/22 and observed that all kits with evidence of intrauterine infection had white matter damage.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Experimentally induced intrauterine infection causes brain damage in neonatal rabbits (54,55), and the administration of endotoxin to neonatal animals is associated with injury to the periventricular white matter (56,57). Notably, the periventricular white matter has very low blood flow even under normal conditions and the density of blood vessels in the white matter is lowest at around 28 wk gestation, about the same time that incidence of periventricular leukomalacia peaks (58,59).…”
Section: Neutropenia Onset and Neuroprotectionmentioning
confidence: 99%